2005
DOI: 10.1159/000086969
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Syndecan-1 Expression Is Associated with Stage and Grade in Colorectal Cancer

Abstract: Objectives: Loss of epithelial heparan sulfate proteoglycan syndecan-1 has been associated with a more aggressive behavior in various cancer forms, but the prognostic significance of syndecan-1 expression in colorectal cancer is unclear. The aim of this study was to evaluate the prognostic value of immunohistochemical syndecan-1 expression in a series of 237 patients with colorectal cancer. Methods: Paraffin-embedded formalin-fixed specimens were stained with a syndecan-1-specific monoclonal antibody, and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
(43 reference statements)
7
34
3
Order By: Relevance
“…Immunohystochemistry studies of almost 240 colorectal patients observed that epithelial syndecan-1 (Syn-1) expression is associated with stage and grade of cancer [15]. Similar results have also been described showing a significant reduction in Syn-1 in severely dysplastic epithelium and colorectal carcinomas compared with adenomas [16].…”
Section: Introductionsupporting
confidence: 58%
“…Immunohystochemistry studies of almost 240 colorectal patients observed that epithelial syndecan-1 (Syn-1) expression is associated with stage and grade of cancer [15]. Similar results have also been described showing a significant reduction in Syn-1 in severely dysplastic epithelium and colorectal carcinomas compared with adenomas [16].…”
Section: Introductionsupporting
confidence: 58%
“…In addition, E-cadherin decrease was associated with the presence of the mucinous component and distant metastases, while syndecan-1 decrease correlated with large size and localization on the right colon. There are several studies supporting the correlation between decreased expression of these two markers and the following clinicopathological characteristics: histological grade and type [4,[10][11][12][13]23], lymph node and distant metastases [12,22,23], TNM stage [22,23], Duke's stage [13] of colon cancer and age [11], gender of the patient [22]. These didn't report connections between syndecan-1 and size or localization of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous CCR studies, decreased E-cadherin expression [4,10,11], decrease or loss of syndecan-1 expression [4,12,13], or elevated Ets-1 expression [6,7,10] predicts a more invasive behavior and poor prognosis. In this work we studied adenomas of different grade and de novo or ex adenoma colon carcinomas.…”
Section: Introductionmentioning
confidence: 93%
“…Although syndecan-1 is upregulated and appears to promote tumorigenesis in breast carcinoma, decreased expression and possible inhibitory functions have also been reported in lung cancer, colorectal cancer, cervical cancer and a variety of other neoplasms (Table 1; Anttonen et al, 2001;Fujiya et al, 2001;Inki et al, 1994;Lundin et al, 2005;Miturski et al, 1998;Numa et al, 2002;Shinyo et al, 2005), suggesting that the ability of syndecan-1 to serve as a prognostic marker is cancertype specific. The expression and role of syndecan-1 in tumorigenesis can also differ within a particular cancer.…”
Section: Syndecan-1mentioning
confidence: 99%